The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1037/0033-2909.106.1.97
|View full text |Cite
|
Sign up to set email alerts
|

Self-statement modification in the treatment of child behavior disorders: A meta-analysis.

Abstract: Reviews 48 outcome studies that applied self-statement modification (SSM) to childhood behavior disorders. Selection criteria restricted the review to controlled experimental studies and to children with disorders of clinically relevant severity. Meta-analysis was used to provide summary information about the observed effects of SSM. Collectively, SSM outcomes surpassed no treatment and placebo treatment by roughly a half of a standard deviation, on the average. Efficacy varied considerably with length of foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
99
1
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(102 citation statements)
references
References 63 publications
1
99
1
1
Order By: Relevance
“…The underlying assumptions are that overt behavior is mediated by cognitive events and that people can learn to influence cognitive events to change their own behavior. Literature reviews and meta-analyses (Abikoff, 1991;Dush, Hirt, & Schroeder, 1989;Robinson et al, 1999;Smith, Lochman, & Daunic, 2005) have substantiated CBI's usefulness for the prevention and remediation of specific behavioral deficits and the maintenance of appropriate behavior for mainstream students. Teaching students cognitive strategies has been found to decrease hyperactivity/impulsivity and disruption/aggression, strengthen pro-social behavior, increase social cognition, and improve peer relations (cf.…”
mentioning
confidence: 99%
“…The underlying assumptions are that overt behavior is mediated by cognitive events and that people can learn to influence cognitive events to change their own behavior. Literature reviews and meta-analyses (Abikoff, 1991;Dush, Hirt, & Schroeder, 1989;Robinson et al, 1999;Smith, Lochman, & Daunic, 2005) have substantiated CBI's usefulness for the prevention and remediation of specific behavioral deficits and the maintenance of appropriate behavior for mainstream students. Teaching students cognitive strategies has been found to decrease hyperactivity/impulsivity and disruption/aggression, strengthen pro-social behavior, increase social cognition, and improve peer relations (cf.…”
mentioning
confidence: 99%
“…The findings suggested that in order to obtain optimal treatment effects from VSI training, the cultural and sub-cultural affiliation or status of the target group may be studied. Manning (1990), Dush et al (1989) had suggested the role or contribution of cultural factors, subject variables, developmental status and mental maturity etc. Which may act as catalyst in moderating the treatment efficacy of VSI.…”
Section: Discussionmentioning
confidence: 99%
“…In general, although it is evident from theoretical perspective and empirical research findings that VSI is an effective method in modifying varieties of childhood problems, there have been several unsuccessful attempts to achieve positive results (i.e., Dulcan 1986). Several theoretical and methodological issues have also been raised in addition to failure to replicate the positive effects of VSI (i.e., Dush, Hirt, & Schroeder, 1989;Rath, 1995). The VSI training consists of multifaceted intervention techniques including modeling, overt and covert rehearsal, prompts, feedback, reinforcement and/or response cost in addition to training the specific task strategies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies investigating other treatment models for children with ED have examined the relationship between the child's demographic (age, gender, ethnicity, living status) and clinical profiles (type and severity of diagnosis) and treatment effects. For example, studies have demonstrated that a child's age at intake influences treatment outcomes in contradictory ways, with some studies showing improvement in cognitive-behavioral treatment response for older youth with behavioral problems (Durlack, Fuhrman, & Lampman, 1991;Dush, Hirt, & Schroeder, 1989;Jayson, Wood, Kroll, Fraser, & Harrington, 1998;Kazdin & Crowley, 1997), while other studies favored improvement in younger children (Dishion & Patterson, 1992;Emslie, Mayes, Laptook, & Batt, 2003;Ruma, Burke, & Thompson, 1996, Southam-Gerow, Kendall, & Weersing, 2001). In addition, ambiguous results have been found in studies examining the impact of the child's gender on treatment outcomes (Dalsgaard, Mortensen, Frydenberg, & Thomsen, 2002;Southam-Gerow et al, 2001;Walrath, Mandell, & Leaf, 2001).…”
Section: Child Characteristics and Treatment Outcomesmentioning
confidence: 99%